Effectiveness of Echinochrome on HFD-Induced Hyperlipidemia in Rats - Sohair R. Fahmy; Nashwah Ismail Zaki; Shaimaa Zakaria Eid; Ayman Saber Mohamed; Sarah S. Hassanein (Natural Products and Bioprospecting, 2019)
Abstract Obesity has been identified with an expanded danger of a progression of illnesses that include different organ-frameworks of the body. In the present examination, we evaluated the hypolipidemic properties of Echinochrome (Ech) pigment in a high-fat diet (HFD) induced hyperlipidemia in rats. After the hyperlipidemic model was set up, rats were haphazardly separated into five groups as follows: normal control group, HFD group, Atorvastatin (ATOR) group (80 mg/kg), Ech group (1 mg/kg) and combined group ATOR + Ech. The outcomes demonstrated that Ech improves lipid profile, liver functions, kidney functions and antioxidant markers of obese rats. The findings of the present investigation indicated that the Ech possesses hypolipidemic potential in obese rats.